Depreciation of Housing: An Empirical Consideration of the Filtering Hypothesis - Margolis, Stephen E. (The Review of Economics and Statistics, 1982)
A SSUMPTIONS regarding the depreciation ,AX rate for housing play an important role in the urban economics literature.1 The notion that houses filter down from higher to lower quality is prevalent in both academic and policy discussions of the nature of urban problems. Yet there has been no attempt to specify which depreciation rates are appropriate to these discussions, and little empirical investigation of depreciation in housing. This paper presents estimates of depreciation rates for housing which are appropriate to consideration of the filtering hypothesis. Estimates of these depreciation rates must be pursued differently from estimates of the depreciation rates for the aggregate capital stock of housing. A brief review of previous studies, which points out some of the difficulties which confound observation of depreciation rates, is presented in section I. Section II discusses specification, and section III describes the data and estimation technique used. Results are presented in section IV. Section V is a brief conclusion.